Mock Up Based on Android Through Multimedia Development Live Cycle : Science Meaningfull Learning - Farida Nur Kumala; Jurina Ibrahim; Hefsi Anggi Ambarwati; Siti Mafulah; Sri Rahayu (Universitas Pendidikan Ganesha, 2023)
Covid 19 has led to loss learning and decreased student motivation in learning so that learning is needed that can increase motivation and meaningfulness in learning. The purpose of this study was to develop an Android-based mock up using the Multimedia Development Live Cycle (MDLC) steps to develop meaningful science learning in elementary schools. This research is a development research using the MDLC stages followed by trials on material, language, media and user experts. The subjects of this study were experts, teachers and 5th grade students. Technical analysis used descriptive quantitative techniques. Data collection methods consist of questionnaires, interviews and tests. Instruments in the form of expert validation sheets, tests, interviews and teacher and student response questionnaires. The results of the study show that the media that has been developed has a material expert feasibility of 68% (appropriate), media expert 91% (very feasible), and language expert 94% (decent). The teacher's practicality assessment obtained a percentage of 87% (very practical) and students obtained a proportion of 77% with very practical criteria. Android-based mock up is feasible to use. This is also based on the results of an increase in the average pretest score of 63.3 and posttest of 77.7. Posttest scores also show scores above the Minimum Completeness Criteria (KKM). Android-based Mock Up can improve student learning outcomes and make science learning more meaningful for students.